Factibilidad del uso de radiofrecuencia en bitúmenes y crudos extrapesados en Colombia (2020)
Colombia has reserves of about 1800 million barrels according to government sources, so it has the possibility of developing additional reserves to have energy sustainability in the near future. This project seeks to establish the commercial applicability of radio frequency technology, studying it from a technical point of view: screening applied to fields in Colombia, economic: landing costs at the Colombian level and making cash flows for the fields of study, and environmental: determining impacts and environmental management plans for extra-heavy oil and bitumen deposits in Colombia, making a comparison against SAGD technology that would be another alternative for the development of this type of field. The conclusion is that it is possible to apply the technique in Colombia, however, depending on the field, it requires a higher oil price than the current one in order to be financially viable.